New ways to image and target tumour hypoxia and its molecular responses. Issue 3 (September 2015) - Dubois, Ludwig J.; Niemans, Raymon; van Kuijk, Simon J.A.; Panth, Kranthi M.; Parvathaneni, Nanda-Kumar; Peeters, Sarah G.J.A.; Zegers, Catharina M.L.; Rekers, Nicolle H.; van Gisbergen, Marike W.; Biemans, Rianne; Lieuwes, Natasja G.; Spiegelberg, Linda; et al.
Abstract Tumour hypoxia and its molecular responses have been shown to be associated with poor prognosis. Detection of hypoxia, preferably in a non-invasive manner, could therefore predict treatment outcome and serve as a tool to individualize treatment. This review gives an overview of recent literature on hypoxia imaging markers currently used in clinical trials. Furthermore, recent progress made in targeting hypoxia (hypoxia-activated prodrugs) or hypoxia response (carbonic anhydrase IX inhibitors) is summarized. Last, window-of-opportunity trials implementing non-invasive imaging are proposed as an important tool to prove anti-tumour efficacy of experimental drugs early during drug development.